Drug‐Mediated Gene Regulation of Vitamin D3 Metabolism in Primary Human Dermal Fibroblasts. Issue 1 (13th September 2016) - Norlin, Maria; Lundqvist, Johan; Ellfolk, Maria; Hellström Pigg, Maritta; Gustafsson, Jan; Wikvall, Kjell
Abstract: Vitamin D metabolism was studied in primary human dermal fibroblasts with focus on drug‐mediated gene regulation related to adverse side effects of antiretroviral drugs used in HIV therapy. The fibroblasts expressed mRNA for cytochrome P450 (CYP) enzymes catalysing bioactivating (CYP2R1, CYP27A1 and CYP27B1) and catabolic reactions (CYP24A1). The cells produced both 25‐hydroxyvitamin D3 and 1α, 25‐dihydroxyvitamin D3 . The results demonstrate that primary dermal fibroblasts have an active vitamin D3 ‐metabolizing system. High incidence of low bone mineral density is a concern for HIV‐infected patients treated with antiretroviral drugs. Osteomalacia and severe vitamin D deficiency have been reported. We investigated whether drug‐mediated gene regulation could be a possible mechanism behind these adverse drug effects. Fibroblasts were treated with different drugs used in HIV therapy, and the 1α, 25‐dihydroxyvitamin D3 levels and relative mRNA levels for crucial enzymes were determined. Efavirenz, stavudine and ritonavir significantly down‐regulated the bioactivating CYP2R1 and up‐regulated the catabolic CYP24A1. The drugs reduced bioactivating enzyme activities and cellular levels of 1α, 25‐dihydroxyvitamin D3 . The current results indicate that effects on gene expression may lead to disturbed vitamin D metabolism and decreased cellular levels of active vitamin D3 . The data are consistent with the impaired bone health in patients treated with certain antiretroviral drugs.